2011
DOI: 10.1002/adma.201103284
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Diagnosis for an Anthrax‐Protective Antigen Based on a Polyvalent Directed Peptide Polymer Coupled to Zinc Oxide Nanorods

Abstract: A flexible poly-D-lysine polymer conjugated with different target-binding peptides is demonstrated with an ultralow concentration detection limit compared to those of other conventional detection systems. This polyvalent directed peptide polymer (PDPP) exhibits increased binding affinity and detects anthrax protective antigen at low levels using a well-known zinc oxide nanorod detection system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…For these reasons, ZnO nanomaterials function to enhance fluorescent signals in the detection of fluorescent-labeled biomolecules , for use in biosensors and biomedical applications. In previous research, ZnO nanomaterials were confirmed to increase fluorescence signals . Herein, a nanoporous ZnO platform was obtained by cation exchange (Zn 2+ ) with CdO architectures, and its XRD pattern is shown in Figure A.…”
Section: Resultsmentioning
confidence: 95%
“…For these reasons, ZnO nanomaterials function to enhance fluorescent signals in the detection of fluorescent-labeled biomolecules , for use in biosensors and biomedical applications. In previous research, ZnO nanomaterials were confirmed to increase fluorescence signals . Herein, a nanoporous ZnO platform was obtained by cation exchange (Zn 2+ ) with CdO architectures, and its XRD pattern is shown in Figure A.…”
Section: Resultsmentioning
confidence: 95%
“…The introduction of nanotechnology has provided enormous opportunities to enhance the performance of biosensors. 27 A polyvalent peptide polymer that was coupled with zinc oxide nanorods allowed for the development of an ultrasensitive fluorescence sensor with a LOD of 15 zM for PA. 28 An electrical graphene aptasensor enabled PA detection with a LOD of 1.2 aM. 29 The combined use of an electrochemical immunosensor with bismuth nanocomposites and cadmiumion-functionalized titanium phosphates enabled detection even at a volume of as low as 50 pg/mL in 35 min.…”
Section: Anthracismentioning
confidence: 99%
“…The introduction of nanotechnology has provided enormous opportunities to enhance the performance of biosensors . A polyvalent peptide polymer that was coupled with zinc oxide nanorods allowed for the development of an ultrasensitive fluorescence sensor with a LOD of 15 zM for PA . An electrical graphene aptasensor enabled PA detection with a LOD of 1.2 aM .…”
Section: Biosensors For Anthrax Toxinsmentioning
confidence: 99%
“…60 Several assays that measure 1 or more of the 3 toxin proteins have been published-for example, antibody microarrays, 61 microwave-accelerated metal-enhanced fluorescence, 62 ELISA, 8 europium nanoparticles based immunoassay, 63 or detection based on polyvalent directed peptide polymer. 64 An activity-based immunoassay for LF has been described by Bagramyan and Kalkum. 65 The method uses commercially available fluorophore-tagged peptides as substrates for LF activity measurement.…”
Section: Clostridial Neurotoxinsmentioning
confidence: 99%